A Exploring the Influence of Locations on Cyanide, Moisture and Microbial Loads of Gari Produced from five Major Processing Areas in Abia State, Nigeria: Processing Location Effect on the Cyanide, Moisture and Microbial Loads of Gari Produced in Different Area in Abia State, Nigeria - Sunday, Onyinyechi; Ndife, Joel; Okwunodulu, Felicia; Okwunodulu, Innocent (Indonesian Food Science and Technology Journal, 2023)
This study investigated the cyanide, moisture and microbial content of white and yellow gari sampled from the five market locations using standard analytical methods. Cyanide levels of white gari samples from Ndoki market location was least (0.122mgHCN) and highest (0.429mgHCN) in Isialangwa market location. Yellow gari samples had the least cyanide content (0.121mgHCN) in Ndoki market location and highest (0.373mgHCN) in Isialangwa market location. Moisture content of white gari samples was least (6.32%) in Ndoki market location and highest (10.16%) in Ndoro market location while yellow gari was least (5.82%) in Uzuakili market location and highest (11.26%) in Ariara market location. Total bacterial count of white gari was least (2.15cfu/g) in Ndoki market location and highest (3.10cfu/g) in Ariara market location. Yellow gari sample was least (2.40cfu/g) in Ndoki market location and highest (3.20cfu/g) in Ariara market location. Total fungi count of white gari was least (1.16cfu/g) in Ndoki market location and highest (2.70cfu/g) in Ariara market location while the yellow gari cyanide was least (1.07cfu/g) in Ndoki market location and highest (2.90cfu/g) in Ariara market location. All the quality indexes evaluated varied significantly (p<005) with market locations and lower than recommended safe limits.